GAMBARAN MAKNA HIDUP PADA LANSIA YANG TINGGAL DI PANTI WERDHA - Marisa Reni Santoso; Stefani Virlia (Psibernetika, 2014)
The meaning of life is important and valuable for everyone, including the elderly. The elderly regarded as a period of decline began to occur where the signs of aging , such as wrinkles, graying hair, illness, and so on. In addition to physical changes, the elderly also experience psychological changes, such as less emotionally stable, depression, loneliness, and so on. These things can affect the elderly in meaning life. This study aims to determine how the image of the meaning of life in the elderly living in nursing homes. This study used a qualitative approach with two elderly subjects living in nursing homes X , Jakarta. Data was collected through interviews and observation techniques and the results were analyzed using content analysis. The results of this study are aspects forming of the meaning of life in the elderly are subjective, some interpret his life by linking the religious aspect, but there is also that to make sense of his life by linking the family aspect . Keywords: elderly, meaning of life, the meaning of life aspects